Psychological constraint on unethical behavior in team-based competition - Zhu, Yi; Zheng, Lijing; Hu, Yu (Frontiers in Psychology, 2023)
A growing body of research contributes to our knowledge about unethical behavior. However, very little is known about how group-based competition shape members’ unethical behavior. Building on social learning theory, we conducted three studies to reveal how group-based competition may affect individual’s unethical behavior for their team. Study 1 and 2 are laboratory experiments in which participants were randomly assigned into groups of three members and engaged in group-based competition (or engaged in individual-based competition in an individual context) with monetary incentives. Different from individual-based competition where mean number of unethical behaviors for the self in the losing condition was larger than that in the winning condition, in group-based competition mean number of unethical behaviors in favor of group between the winning and the losing condition was not significantly different. Both studies also showed that there are less unethical behaviors in the group-based competition than in the individual-based competition. Study 2 further revealed that collective efficacy negatively associated with mean number of unethical behaviors in group-based competition. Study 3 was a field study with employees from bank subsidiaries working as teams, and results from their self-reported data confirm the relationship between collective efficacy and unethical behaviors observed in Study 2. Together, these results suggest that collective efficacy has the effect of curbing unethical behavior in group-based competition, thus contributing to the understanding of group-based experience on unethical behaviors.